2020
DOI: 10.1111/1751-7915.13672
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis and Enterococcus faecium co‐fermented feed regulates lactating sow's performance, immune status and gut microbiota

Abstract: Fermented feed (FF) is widely applied to improve swine performance. However, the understandings of the effects of FF on the immune status and gut microbiota of lactating sows and whether probiotics are the effective composition of FF are still limited. The present study aimed to investigate the performance, immune status and gut microbiota of lactating sows fed with a basal diet supplemented with Bacillus subtilis and Enterococcus faecium co-fermented feed (FF), with the probiotic combination (PRO) of B. subti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 55 publications
3
22
0
1
Order By: Relevance
“…There was a reduction in the incidence of constipation in sows and diarrhea in piglets, which was related to the modulation of the intestinal microflora. The sows showed better immunity and performance compared to the control [ 84 ]. Another experiment used the positive effects of Bacillus coagulans , oregano oil, and benzoic acid on the health, physiological, and physical condition of the piglets.…”
Section: Prevention Of the Effects Of Piglet Weaning Based On The Use Of Labmentioning
confidence: 99%
“…There was a reduction in the incidence of constipation in sows and diarrhea in piglets, which was related to the modulation of the intestinal microflora. The sows showed better immunity and performance compared to the control [ 84 ]. Another experiment used the positive effects of Bacillus coagulans , oregano oil, and benzoic acid on the health, physiological, and physical condition of the piglets.…”
Section: Prevention Of the Effects Of Piglet Weaning Based On The Use Of Labmentioning
confidence: 99%
“…Proporcingai didėjant probiotiko suvartojimui didėjo kiaušinių svoris, vaisingumas, kiaušinių išsiritimas, kiaušinių lukšto stiprumas, progesterono ir liuteinizuojančio hormono kiekis kraujyje . Dar vienas Bacillus kultūros teigiamas poveikis yra tai, kad jo suvartojimas didina gyvūnų svorį, mažina vidurių užkietėjimą bei sudaro atsparumą prieš dar vieną patogeną -Enterobacteriaceae, ir didina Lactobacillus ir Succiniclasticum kolonijų kiekį, kuris yra nepaprastai susijęs su augimo rezultatais ir kraujo imuniniais parametrais (Wang, 2021). Tyrimo problemamodernizacijos svarba ir iššūkiai konteinerių terminaluose.…”
Section: Panaudojimas Pašarų Gamybojeunclassified
“…Previous research has shown the beneficial effects of a combined live B. subtilis R-179 and E. faecium R-026 on host health (Guo et al, 2018;Wang et al, 2021). Live combined B. subtilis and E. faecium (LCBE) strains are approved for use as animal feed additives (Jensen and Bjørnvad, 2019).…”
Section: Introductionmentioning
confidence: 99%